Guidelines to use tomato in experiments with a controlled environment - Schwarz, Dietmar; Thompson, Andrew J.; Kläring, Hans-Peter (Frontiers in Plant Science, 2014)
Domesticated tomato (Solanum lycopersicum) is the most important horticultural crop worldwide. Low polymorphism at the DNA level conflicts with the wealth of morphological variation. Fruits vary widely in size, shape and colour. In contrast, genetic variation between the 16 wild relatives is tremendous. Several large seed banks provide tomato germplasm for both domesticated and wild accessions of tomato. Recently, the genomes of the inbred cultivar “Heinz 1706” (≈900 Mb) and S. pimpinellifolium (739 Mb) were sequenced. Genomic markers and genome re-sequencing data are available for >150 cultivars and accessions. Transformation of tomato is relatively easy and T-DNA insertion line collections are available. Tomato is widely used as a model crop for fruit development but also for diverse physiological, cellular, biochemical, molecular and genetic studies. It can be easily grown in greenhouses or growth chambers. Plants grow, flower, and develop fruits well at daily light lengths between 8-16 hours. The required daily light integral of an experiment depends on growth stage and temperature investigated. Temperature must be 10-35°C, relative humidity 30-90 % and CO2 concentration 200-1500 µmol mol-1. Temperature determines the speed of the phenological development while daily light integral and CO2 concentration affect photosynthesis and biomass production. Seed to seed cultivation takes 100 days at 20°C and can be shortened or delayed by temperature. Tomato may be cultivated in soil, substrates, or aeroponically without any substrate. Root volume and water uptake requirements are primarily determined by transpiration demands of the plants. Many nutrient supply recipes and strategies are available to ensure sufficient supply as well as specific nutrient deficits/surplus. Using appropriate cultivation techniques makes tomato a convenient model plant for researchers, even for beginners.